Transformasi Akad Tabarru’, Qardh, dan Rahn dalam Era Digital: Analisis Fikih atas Tradisi Ringgit Emas Masyarakat Makassar: The Transformation of Tabarru’, Qardh, and Rahn Contracts in the Digital Era: A Fiqh Analysis of the Ringgit Emas Tradition in Makassar Society - Nurul Husna; Muhammad Yazid (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
Ringgit Emas is a traditional debt-based practice in Makassar society rooted in trust and communal values. However, the rise of digital economics and the transformation of Islamic financial systems necessitate a renewed analysis of the underlying contracts, particularly tabarru’, qardh, and rahn. This study aims to examine the Ringgit Emas tradition through the lens of classical Islamic jurisprudence and assess its relevance within the ecosystem of digital Islamic finance. This research employs a qualitative-descriptive approach supported by literature review and normative analysis. The findings reveal that Ringgit Emas embodies the spirit of mutual assistance (tabarru’) aligned with the objectives of Islamic law (maqāṣid al-syarī‘ah), yet its practice often shifts toward burdensome and inequitable arrangements. In the digital context, qardh and rahn have undergone significant transformation through Islamic fintech platforms, digital gold collateral systems, and enhanced technology-based security mechanisms. This study concludes that Ringgit Emas can remain culturally preserved as long as its contracts are reconstructed to be more transparent, fair, and compatible with modern Islamic financial principles.